Dpal Gsan ba ʼdus paʼi rgyud ʼgrel le daṅ yan gyi gsal sgron bźugs pa yin lags - ʼJam-dbyaṅs-grags-pa-rgyal-mtshan, Sdog-ston (Kunsang Topgyel and Mani Dorji, 1979)
Commentary on the 1st chapter of the Guhyasamājatantra, Buddhist tantric text.